ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMILIHAN JASA PENGIRIMAN BARANG - Maria Regina Nansi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Freight forwarding services have become one of the most shining businesses amid a pandemic that has hit the world. The habits of face-to-face consumer and producer transactions are forced to change drastically into online transactions to maintain public health and make social restrictions a success. Another impact of this booming business is the competition that all business delivery services must face. This study aims to determine and analyze the service factors that influence consumer decisions in choosing goods delivery services. Further, from the solutions to the problems that have occurred so far, it is hoped that research can be taken. The research method uses descriptive research with a qualitative approach in the case study design. The results of this study indicate that the factors that influence consumers in choosing delivery services at DPL Translogistics are 1) on-time delivery, 2) security of delivery of goods, 3) image/brand, 4) ease of access to location, 5) service price, 6) area/destination of delivery, 7) monitoring of delivery of goods, 8) insurance, 9) speed of service, 10) response to consumer complaints, 11) various services, 12) various packing and re-packing services, 13) employee empathy, 14 ) employee competence, 15) employee professionalism, 16) office facilities, 17) easy access to contact persons, 18) employee appearance, and 19) fleet variation. To be able to maintain market share and maintain service excellence and customer satisfaction, DPL must always understand the changing needs of customers, especially in terms of competitive prices/shipping rates and better service quality. DPL must also follow developments in the digital world by improving website connections and adding digitalized services.